Postoperative and Recurrent Hematuria after Pretransplant Core Needle Biopsy in Living Donor Kidney Transplant. (28th July 2022) - Al-Adwan, Yazan; Singh, Navdeep; Chotai, Pranit N.; Siddiqui, Farjad; Limkemann, Ashley; Schenk, Austin; Subramanian, Jayanthan; Washburn, W. Kenneth; Alebrahim, Musab; Rajab, Amer
Abstract : Background . Core needle and wedge biopsies are the two main pathologic ways to determine the suitability of a kidney allograft and to have a baseline allograft biopsy in case of future rejection. Case Presentation . A 57-year-old patient developed a renal arteriovenous fistula causing postoperative and recurrent hematuria after allograft pretransplant renal core needle biopsy and treated with selective Interventional radiology coil embolization. Conclusion . Delayed profound hematuria can be seen after pretransplant core needle renal biopsies and can recur again even after complete resolution, due to arteriovenous fistula formation in the renal calyceal system.